2005
DOI: 10.1186/1471-2490-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Casodex treatment induces hypoxia-related gene expression in the LNCaP prostate cancer progression model

Abstract: Background: The changes in gene expression profile as prostate cancer progresses from an androgen-dependent disease to an androgen-independent disease are still largely unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…We hypothesised that some of the differences seen between the metastatic and localised cohorts were as a result of androgen regulation of the identified genes. This was investigated using published ChIP-seq data, which showed strong AR binding to the FAM129A and MME loci in multiple cell lines consistent with previous reports of altered regulation of FAM129A in cells treated with the anti-androgen, bicalutamide (Rothermund et al 2005, Wang et al 2009, Yu et al 2010, Massie et al 2011. This also suggests that MME and FAM129A are novel androgen-regulated genes, and this was confirmed by demonstrating enrichment of AR binding to the MME, FAM129A and KRT7 promoters following treatment with androgen ( Fig.…”
Section: Discussionsupporting
confidence: 81%
“…We hypothesised that some of the differences seen between the metastatic and localised cohorts were as a result of androgen regulation of the identified genes. This was investigated using published ChIP-seq data, which showed strong AR binding to the FAM129A and MME loci in multiple cell lines consistent with previous reports of altered regulation of FAM129A in cells treated with the anti-androgen, bicalutamide (Rothermund et al 2005, Wang et al 2009, Yu et al 2010, Massie et al 2011. This also suggests that MME and FAM129A are novel androgen-regulated genes, and this was confirmed by demonstrating enrichment of AR binding to the MME, FAM129A and KRT7 promoters following treatment with androgen ( Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Importantly, androgen ablation by castration induces hypoxia caused by reduced blood flow to the prostate tissue [ 43 , 44 ]. Similarly, anti-androgen casodex treatment increased the expression of hypoxia signature genes in LNCaP cells [ 45 ]. Mitani et al reported that hypoxia enhances AR transcriptional activity under low androgen conditions, mimicking the androgen independence stage [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the multidrug resistance 1 gene has been observed to be hypoxia-respon- sive and is regulated by HIF-1␣ (30). Treatment of LNCaP cells with the androgen receptor antagonist Casodex results in up-regulation of a subset of hypoxia-related genes, including membrane metallo-endopeptidase and cyclin G2, which might be involved in development of the androgen-independent phenotype (31).…”
Section: Discussionmentioning
confidence: 99%